ANALYSIS OF THERESIAN GENERAL HEALTH REGULATIONS FROM 1770 AND HEALTH REGULATIONS IN CROATIA AND SLAVONIA DURING THE SECOND HALF OF THE 19TH CENTURY - Čandrlić, Slavko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Abstract: In the introductory part of the work, the assumption of power by the Empress and Queen Maria Theresa is presented and her reforms in the field of health are explained. Particular attention is paid to the adoption of the General Health Ordinance of 1770, which unified all previous health regulations into one valid for the entire Habsburg Monarchy. In the further course of the work, the legal provisions of the aforementioned ordinance, which regulated health care, are presented in detail. Furthermore, the importance of the Croatian-Hungarian Compromise of 1868 and the creation of a legal basis for the development of further health reforms is explained, which is why the Health Care Regulation Act was first enacted in 1874 and the Health Care Service Regulation Act, the Pharmacy Act and other accompanying health regulations in 1894.